Oxygen Desaturation Is Associated With Fibrocyte Activation via Epidermal Growth Factor Receptor/Hypoxia-Inducible Factor-1α Axis in Chronic Obstructive Pulmonary Disease - Wang, Chun-Hua; Lo, Chun-Yu; Huang, Hung-Yu; Wang, Tsai-Yu; Weng, Chih-Ming; Chen, Chih-Jung; Huang, Yu-Chen; Chung, Fu-Tsai; Lin, Chang-Wei; Chung, Kian Fan; Kuo, Han-Pin (Frontiers in Immunology, 2022)
Fibrocytes are bloodborne mesenchymal progenitors which accumulate and differentiate at disease site. We investigated whether hypoxemia activates fibrocytes, accelerating airflow limitation and exercise intolerance in chronic obstructive pulmonary disease (COPD) patients. Flow cytometry was used to determine collagen I+/CD45+ fibrocytes and α-smooth muscle actin+ differentiating fibrocytes within peripheral blood and cultured cells, as well as the expression of CXC chemokine receptor 4 (CXCR4), epidermal growth factor receptor (EGFR), connective tissue growth factor (CTGF) and hypoxia-inducible factor (HIF)-1α. Fibrocytes in lung specimens were identified by confocal microscopy. Compared to non-desaturators, COPD desaturators (peripheral blood oxygen saturation ≤88% during exercise) had greater number of fibrocytes in peripheral blood and lung specimens, paralleled with faster yearly lung function decline and 6-minute walk distance. Fibrocytes from desaturators expressed more EGFR, CXCR4, CTGF and HIF-1α, with a higher capacity of proliferation and myofibroblastic differentiation. Hypoxia (5% oxygen) increased the expression of EGFR, CXCR4, CTGF and HIF-1α, the number and differentiation in fibrocytes. These effects were attenuated by EGFR inhibitor gefitinib, HIF-1α gene silencing, and anti-CTGF antibody. These data elucidate that hypoxemia triggers fibrocyte activation through the EGFR/HIF-1α axis, aggravating airflow obstruction in COPD.